Religious Organisations and Corporate Social Responsibility during Covid-19 Lockdown: A Survey of Christians in South-Southern Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
This study was designed to appraise religious organisation’s corporate social responsibility efforts during the COVID-19 lockdown in the South-South Nigeria. The objectives of this study were to determine the corporate social responsibility obligations of religious organisations in south-southern Nigeria, how the religious organisations were dispensing their social responsibility obligations to the citizenry during the COVID-19 period, how often these social corporate responsibility obligations met the expectations of the citizen, the effects of corporate social responsibility on behavioural change of church membership. The descriptive survey research method was adopted with the questionnaire as the research instrument. The South-South region of Nigeria constituted the population of the study while a sample size of 400 respondents from the Taro Yamane formula were selected. However, 381 copies of the questionnaire were returned and certified as appropriate for the study. The study adopted the proportional sampling techniques. The findings of the study revealed that a majority of the respondents (57%) received assistance from various religious organisations during the lockdown though there were significant disparities in their areas of interest. The study concluded that the CRS initiatives of the religious organisation positively influenced their images and fostered a sense of care and compassion which led to new member enrolment. It was recommended among others that religious organisations should improve the timeliness of their support during emergencies while such initiatives should be carried out with more transparency.